رسول اللہ صلیٰ اللہ علیہ وسلم کی قبر انور سے صحابہ کرام رضی اللہ عنہ کے تبرک و تعامل کا تحقیقی مطالعہ - معبوب الرحمٰن، ڈاکٹر محمد سجاد, (Seerat Studies, 2024)
The Shrine of The Holy Prophet Hadharat Muhammad SAAWAS is one of the holiest and blessed places in the world for Muslims. This is the place where the last Prophet of Allah was laid down for rest till the Day of Judgment. Millions of Muslims from all over the world come to Medina Munawara every year to visit this holy place and to offer Darood o Salam to their beloved Prophet and to pray to Allah before this sacred place. It has been a usual practice for the Sahaba to be blessed and to get Tabarruk from The Holy Prophet and His belongings. Sahaba continued this practice even after the departure of The Prophet (peace and blessings of Allah be upon Him) from this world. This article deals with the practice of Sahaba regarding Tabarruk from the shrine of Holy Prophet Muhammad SAAWAS۔